Lymphoma of the Cervix - Parnis, Juanita; Camilleri, David J.; Babic, Darko; DeGaetano, James; Savona-Ventura, Charles (Case Reports in Hematology, 2012)
Primary non-Hodgkins lymphoma of the uterine cervix is a very rare diagnosis. A 54-year-old woman presented with a 3-month history of postmenopausal bleeding per vaginum. On examination, a friable, fungating lesion was seen on the cervix. Histology revealed a CD 20 positive high-grade non-Hodgkin’s diffuse large B cell lymphoma from cervical biopsies and endometrial curettage. She was diagnosed as stage IE after workup and subsequently treated with six cycles of R-CHOP chemotherapy followed by radiotherapy of the involved field.